Analisis Laporan Keuangan untuk Menilai Kinerja pada PT. Bank Mandiri Taspen Cabang Makassar - Andi Alamsyah Saputra; Masdar Ryketeng (Journal of Accounting, Economics, and Business Education, 2023)
This study aims to determine the effect of solvency, profitability, leverage, and firm size on the accuracy of financial statement submissions. The research was conducted at the company PT. Bank Mandiri Taspen Makassar Branch for the 2017-2019 period. The more precise the financial statements are submitted, the more useful the information presented will be for users in making decisions. The sampling technique used was the purposive sampling method. The results showed that the submission of the financial statements of PT. Bank Mandiri Taspen Makassar Branch and company size have a positive effect on financial performance at Bank Mandiri Taspen Makassar Branch. While solvency, profitability, and liquidity have no effect on financial performance.